Caspases and caspase regulators in Lepidoptera and Diptera - Bryant, William Barton (Kansas State University, 2010)
Apoptosis is an extremely conserved process among metazoans. This dissertation will describe apoptotic regulation in two orders of insects, Lepidoptera and Diptera. In the lepidopteran host Trichoplusia ni, we describe phenotypes of infection with the baculovirus AcMNPV lacking the caspase inhibitor gene P35. In the lepidopteran host Spodoptera frugiperda, infection with this mutant virus results in apoptosis, which dramatically hinders spread of the virus in the host. In T. ni, however, infection with this mutant virus is similar to wild-type with normal spread, but the end result of liquefaction does not occur. Experiments indicated that infection of T. ni cells with the P35 mutant virus (P35Δ) resulted in caspase activation, and the P35Δ virus lacked the ability to inhibit these active caspases. With the P35Δ virus a slower entry phenotype was observed, but when the P35Δ virus was grown in the presence of a caspase inhibitor the entry phenotype was rescued. This indicated that caspases have detrimental effects on budded virions, and illustrated that P35 is needed to make robust virions. With regards to Diptera, apoptosis-regulatory genes were annotated in the yellow fever mosquito, Aedes aegypti. The genes annotated included multiple caspases and caspase regulators. Phylogenetic relationships were determined among the caspases from Anopheles gambiae, Ae. aegypti and Drosophila melanogaster, expression patterns were determined for all the annotated genes in Ae. aegypti, and one of the genes, an IAP antagonist named IMP, was functionally characterized. Further characterization of the phylogenetic relationships of caspases from fifteen dipteran species was performed by obtaining gene models for caspases of recently sequenced genomes for twelve Drosophila species and three mosquito species. Furthermore, several Drosophila and mosquito species were found to contain caspase genes with substitutions in critical active site residues. These genes were proposed to encode caspase-like decoy molecules. While these have been found in humans and nematodes, this is the first report for these molecules in insects. One of the caspase-like decoy molecules was found to increase the activity of its paralog caspase.
Keywords: Apoptosis; Aedes aegypti; AcMNPV; P35; Caspase; Caspase-like decoy molecules; Biology, Cell (0379); Biology, Entomology (0353); Biology, Molecular (0307)